LITERATURA COMPARADA ONTEM E HOJE: CAMPO EPISTEMOLÓGICO DE ANSIEDADES E INCERTEZAS - Alós, Anselmo Peres (Organon, 2012)
ABSTRACT: this paper aims at discussing some critical points when it comes to the development of the comparative literature from its origins until the contemporary anxieties of the discipline. It is also discussed here some of the non-eurocentric theoretical contributions, which are extremely relevant to the discipline in these times hauted by the epistemic incertitudes of the 21st century.